Energy absorption of self-similar inspired multi-cell tubes under quasi-static and dynamic loading - He Yulong; Jin Tao; Sun Jiapeng; Li Xin; Qiu Ji; Shu Xuefeng; Liu Yajun (Journal of Materials Research and Technology, 2022)
Self-similar multi-cell structures have been widely applied in engineering fields for their excellent mechanical properties and multi-functional characteristics. In this paper, self-similar inspired multi-cell tubes are constructed by replacing the substructures according to different strategies. The hybrid tubes are built by the space-filling and tessellation of these self-similar inspired multi-cell tubes. The effect of the diameter, layout and hierarchical order are experimentally investigated. The tessellation and space-filling of these multi-cell tubes are numerically and theoretically investigated. The results show that the specific energy absorption (SEA) increases with the hierarchical fractal order. The specific energy absorption of the 2nd order self-similar inspired multi-cell tubes increased by 342.5% and 116.5% compared to the 0th and 1st order multi-cell tubes. It is also found that the increase of the side length is not an effective method to improve the crashworthiness of the lower-order multi-cell tubes. Finally, a theoretical model of the angle element was constructed to predict the mean crushing force of these multi-cell tubes. In general, our research provides an effective method for the design of self-similar inspired multi-cell structures with excellent crashworthiness.